The dark forest ebook - Liu, Cixin (Remembrance of Earth's Past, 2015)
The inspiration for the Netflix series 3 Body Problem ! Over 1 million copies of the Three-Body Problem series sold in North America PRAISE FOR THE THREE-BODY PROBLEM SERIES: "A mind-bending epic." — The New York Times " War of the Worlds for the 21st century." — The Wall Street Journal "Fascinating." — TIME "Extraordinary." — The New Yorker "Wildly imaginative." —Barack Obama "Provocative." — Slate "A breakthrough book." —George R. R. Martin "Impossible to put down." — GQ "Absolutely mind-unfolding." — NPR "You should be reading Liu Cixin." — The Washington Post The Dark Forest is the second novel in the groundbreaking, Hugo Award-winning series from China's most beloved science fiction author, Cixin Liu. In The Dark Forest , Earth is reeling from the revelation of a coming alien invasion-in just four centuries' time. The aliens' human collaborators may have been defeated, but the presence of the sophons, the subatomic particles that allow Trisolaris instant access to all human information, means that Earth's defense plans are totally exposed to the enemy. Only the human mind remains a secret. This is the motivation for the Wallfacer Project, a daring plan that grants four men enormous resources to design secret strategies, hidden through deceit and misdirection from Earth and Trisolaris alike. Three of the Wallfacers are influential statesmen and scientists, but the fourth is a total unknown. Luo Ji, an unambitious Chinese astronomer and sociologist, is baffled by his new status. All he knows is that he's the one Wallfacer that Trisolaris wants dead. The Three-Body Problem Series The Three-Body Problem The Dark Forest Death's End Other Books by Cixin Liu Ball Lightning Supernova Era To Hold Up the Sky The Wandering Earth A View from the Stars At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.